2008
DOI: 10.1017/s1751731108002310
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recombinant caspase 3 on myofibrillar proteins in porcine skeletal muscle

Abstract: The objective of this study was to investigate the potential role of the caspase protease family in meat tenderisation by examining if caspase 3 was capable of causing myofibril protein degradation. Full-length human recombinant caspase 3 (rC3) was expressed in Escherichia coli and purified. The rC3 was active in the presence of myofibrils isolated from porcine longissimus dorsi muscle (LD) and retained activity in a buffer system closely mimicking post mortem conditions. The effect of increasing concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 38 publications
(50 reference statements)
2
36
1
2
Order By: Relevance
“…Caspases 3 and 6 were both identified to cause significant degradation of the large structural proteins titin and nebulin; however degradation patterns of other myofibrillar proteins differed. Caspase 6 induced greater degradation of the intermediate filament protein desmin, in comparison to caspase 3, whilst the appearance of proteolytic fragments at 32 and 28 kDa, previously identified to originate from actin and troponin T degradation respectively (Kemp & Parr, 2008), was significantly higher in the caspase 3 incubated samples. Thus, whilst caspases 3 and 6 can both produce myofibril degradation, their patterns are distinct from one another, highlighting both the differences and also the similarities between these caspases in their target substrate specificity.…”
Section: Caspase-mediated Post-mortem Proteolysismentioning
confidence: 70%
See 2 more Smart Citations
“…Caspases 3 and 6 were both identified to cause significant degradation of the large structural proteins titin and nebulin; however degradation patterns of other myofibrillar proteins differed. Caspase 6 induced greater degradation of the intermediate filament protein desmin, in comparison to caspase 3, whilst the appearance of proteolytic fragments at 32 and 28 kDa, previously identified to originate from actin and troponin T degradation respectively (Kemp & Parr, 2008), was significantly higher in the caspase 3 incubated samples. Thus, whilst caspases 3 and 6 can both produce myofibril degradation, their patterns are distinct from one another, highlighting both the differences and also the similarities between these caspases in their target substrate specificity.…”
Section: Caspase-mediated Post-mortem Proteolysismentioning
confidence: 70%
“…Recently there have been a number of studies examining this benchmark using myofibrils purified from sheep, pigs, chicken and cattle muscle. In porcine LD myofibrils co-incubated with recombinant caspase 3; Kemp and Parr (2008) demonstrated caspases ability to replicate myofibril degradation patterns in situ. MALDI-TOF mass spectrometry identified degradation of myofibril proteins including desmin and troponin I, and proteolytic products at 32, 28 and 18 kDa, found to arise from the degradation of actin, troponin T and myosin light chain, respectively.…”
Section: Caspase-mediated Post-mortem Proteolysismentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown the apoptosis setup in PM skeletal muscle cells by observing a rapid phosphatidylserine externalization, terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labeling positive nuclei, condensation and margination of nuclear chromatin, and progressive degradation of actin, which are considered as typical features of apoptosis (Becila et al, 2010;Cao et al, 2010). In addition, caspases have been demonstrated to be activated during PM storage of meat (Huang et al, 2014;Kemp, Parr, Bardsley, & Buttery, 2006) and involved in PM tenderization in the initial stages of the muscle to meat conversion (Huang, Huang, Ma, Xu, & Zhou, 2012;Huang, Huang, Zhou, Xu, & Xue, 2011;Kemp & Parr, 2008). However, the activation of effector caspases is a complicated process mediated by a series of initiator caspases and apoptotic factors, and the mechanism of which must be elucidated to regulate the aging process through the caspase system.…”
Section: Introductionmentioning
confidence: 98%
“…Due to their abilities to protect cellular proteins from denaturation and loss of function, HSP expression is upregulated in living tissues in response to stress. It is speculated that HSP expression could be stimulated after slaughter in response to the muscle cell stress and death during the conversion of muscle to meat and resulted in the degradation of desmin, troponin I, actin, troponin T, and myosin light chains under in vitro conditions similar to those found in muscle during postmortem aging (Kemp and Parr 2008 ). One study investigated the in vivo behavior of the caspase system by measuring caspase 3/7 and caspase 9 activities and the degradation of caspase substrates, alpha II spectrin, and poly (ADP -ribose) polymerase (PARP) in porcine longissimus muscle between 0 and 8 days postmortem (Kemp et al 2006b ).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%